Reaksi Cairan Jeruk Lemon (C6H8O7) dan NaoH terhadap Tegangan dan Arus yang Dihasilkan dengan Penambahan Katalis Karbon Aktif - Amiruddin, Muhammad Agung; Irawan, Yudy Surya; Wardana, I Nyoman Gede (Rekayasa Mesin, 2020)
Lemon is an environmentally friendly electrolyte. However, an innovative concept is needed to improve the quality of lemon electrolytes. The purpose of this study is to investigate the effect of activated carbon catalyst addition on the voltage and current electric generated from liquid lemon (C6H8O7) and NaOH. Lemon juice group containing acetone (C3H5O) and 3 carboxylic acid group (COOH). The experimental study was performed using voltaic cells. The data measured is 125 ml of an electrolyte solution of lemon juice (C6H8O7) and NaOH 10 grams. To the solution was added 5 grams, 7.5 grams and 10 grams of activated carbon catalyst. The results showed that the addition of activated carbon can accelerate the breaking molecular bond NaOH and C3H5O (COOH)3 which decomposes into ions react with NaCH2COO + and Cu 2+ cathode into a reductant then OH- from NaOH reacts with the anode Zn2++2e be the oxidant While H2O react exothermically. Produces a voltage between 800-1130 mV second. It occurs when electrons flow from the anode interested Zn2+ + 2e react with H2O and of Â Zn2+ + 2e electrons pass led and resistor toward the cathode Cu2+. Cathode Cu 2+ reacts with C6H8O7 and NaOH. The currents that produced ranged from 33.846 to 43.462 mA second. The mechanism of this voltage and current generation makes LED light was on.